The concept of evidence in criminal process (Journal of actual problems of jurisprudence, 2018)
In this article, the authors analyze the different opinions of legal scholars on the concept of proof, they outlined their views and recommendations brought about the concept and content of the evidence in criminal proceedings.Key words: criminal procedure, evidence, proof, substantiation, factual data.